MAP Kinase Phosphatase 3 (MKP3) Preserves Norepinephrine Transporter Activity by Modulating ERK1/2 Kinase-Mediated Gene Expression - Mortensen, Ole V.; Larsen, Mads B.; Amara, Susan G. (Frontiers in Cellular Neuroscience, 2017)
The norepinephrine transporter (NET) mediates the clearance of norepinephrine from the extracellular space and is a target of therapeutic antidepressants and psychostimulants. Previously we identified a MAP kinase phosphatase, MKP3, as an important modulator of protein kinase C (PKC) mediated internalization of the related dopamine transporter (DAT). Here we show that MKP3 decreases PKC-mediated down regulation of NET expressed in PC12 cells. We demonstrate that this process involves PKC-stimulated decrease of NET surface expression that is dependent on dynamin. Surprisingly, MAP kinase inhibitors has no effect on the PKC-mediated regulation of NET activity, suggesting that, like PKC-mediated regulation of the DAT, the acute activation of MAP kinases is not likely to be involved. To elucidate potential mechanisms we used a substrate trap-based assay to identify ERK1/2 as the predominant substrate of MKP3. Furthermore we also established that brief chemical stabilization of a modified destabilized MKP3 does not alter PKC-mediated down regulation of NET. Finally, the expression of a dominant negative version of H-Ras, an upstream activator of ERK1/2, abolishes PMA-mediated down regulation of NET in a manner similar to MKP3. Taken together we propose that chronic MKP3 expression regulates surface NET through the sustained inhibition of ERK1/2 map kinase signaling that alters gene expression in PC12 cells. This is supported by gene expression data from naïve and MKP3-expressing PC12 cells that reveal robust decreases in gene expression of several genes in the MKP3-tranfected cells. Interestingly, caveolin-1, a protein with a critical role in membrane protein trafficking is down regulated by MKP3 expression. We further show that selective silencing of the caveolin-1 gene in naïve PC12 cells attenuates PKC-mediated downregulation of NET activity, consistent with a potential role for caveolins in regulating NET surface expression. In summary, these results suggest that chronic MKP3 expression alters the expression of genes in PC12 cells that are involved in the regulation of NET surface expression.